CHOOSING THE OPTIMAL METHOD OF PROSTHETICS ON IMPLANTS, BASED ON THE INDIVIDUAL CHARACTERISTICS OF THE PATIENT - Kasimova Shakhnoza Odiljon kizi, Kubaev Aziz Saidolimovich; Teshaboev Mukhammadyakhyo Gulomkodirovich (Journals Park Publishing, 2022)
Today, dental implantation is one of the most modern methods of treating patients with partial and complete adentia. At the same time, orthopedic aspects of implantology are described little in the available literature, while more attention is paid to the surgical part of implantology. In this regard, in this review, special attention is paid to prosthetics with support on implants.
Keywords: dental implantology, screw fixation, non-removable fixation of an orthopedic structure with support on implants.